A theoretical study on the feed ratio of dimethyl ether carbonylation on H-MOR zeolites. (3rd May 2021) - Wang, Wei; Qian, Weixing; Ma, Hongfang; Ying, Weiyong; Zhang, Haitao
Abstract : Monte Carlo and molecular dynamics simulations were performed for the adsorption-diffusion properties of dimethyl ether (DME) and carbon monoxide (CO) pure gas and mixture with different feed ratio in H-MOR zeolite to find out the influence of feed ratio on the DME carbonylation activity. For pure gas, DME adsorbs stronger than CO with a competitive adsorption, and all molecules have relatively good diffusion properties. For the mixture, in low feed ratio ( P CO / P DME = 1–10), the adsorption capacity of CO in 8-MR cannot meet the reaction requirement caused the low carbonylation activity, while increasing the feed ratio (to P CO / P DME = 20–30) will promote CO adsorption. The optimal feed ratio P CO / P DME ≈ 27:1 is also discovered. Furthermore, it can also reduce the total molecular per cell and improve the diffusion in each channel which is another factor for the carbonylation activity improvement. Highlights: The adsorption ratio of NCO /NDME in H-MOR was investigated from both adsorption and diffusion sides, which is the key factor affecting the activity of DME carbonylation. A new scheme was proposed to optimise the carbonylation activity by changing the feed ratio, and the mechanism of increase and decrease of feed ratio was analysed from a microscopic point of view. The optimal feed ratio P CO / P DME ≈ 27:1 for DME carbonylation in H-MOR was discovered. A wide range of experimental feed ratio data (covers P CO / P DME = 1:1 to P CO / P DME = 1:50), so this research work provides a new idea for the next subsequent modification of H-MOR, which is to reduce the optimal feed ratio to an acceptable level. GRAPHICAL ABSTRACT: